Defect engineering in thermoelectric materials: what have we learned? - Zheng, Yun (2022)
Thermoelectric energy conversion is an all solid-state technology that relies on exceptional semiconductor materials that are generally optimized through sophisticated strategies involving the engineering of defects in their structure. In this review, we summarize the recent advances of defect engineering to improve the thermoelectric (TE) performance and mechanical properties of inorganic materials. First, we introduce the various types of defects categorized by dimensionality, i.e. point defects (vacancies, interstitials, and antisites), dislocations, planar defects (twin boundaries, stacking faults and grain boundaries), and volume defects (precipitation and voids). Next, we discuss the advanced methods for characterizing defects in TE materials. Subsequently, we elaborate on the influences of defect engineering on the electrical and thermal transport properties as well as mechanical performance of TE materials. In the end, we discuss the outlook for the future development of defect engineering to further advance the TE field.